Video In Situ Snowfall Sensor (VISSS) data for Ny-Ålesund on 2023-08-12 - Maximilian Maahn; Nina Maherndl (PANGAEA, 2024)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Ny-Ålesund. For further details on the VISS Sensor see Maahn et al. (2024).
In: Maahn, M; Maherndl, N (2024): Video In Situ Snowfall Sensor (VISSS) data for Ny-Ålesund (July 2022 - December 2023) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.965766